A block copolymer of zwitterionic polyphosphoester and polylactic acid for drug delivery1. (16th July 2015) - Sun, Rong; Du, Xiao-Jiao; Sun, Chun-Yang; Shen, Song; Liu, Yang; Yang, Xian-Zhu; Bao, Yan; Zhu, Yan-Hua; Wang, Jun
<x xml:space="preserve">Abstract</x> Zwitterionic polyphosphoester containing polymers are synthesized and evaluated as an alternative to poly(ethylene glycol) block copolymers for anticancer drug delivery.